Continuum mechanics based beam elements for linear and nonlinear analyses of multi-layered composite beams with interlayer slips. (1st March 2020) - Kim, Hyo-Jin; Yoon, Kyungho; Lee, Phill-Seung
Abstract: In this study, we present continuum mechanics based beam elements for linear and nonlinear analyses of multi-layered composite beams with interlayer slips. Nonlinear kinematics of multi-layered beams allowing interlayer slips and the finite element formulation for nonlinear incremental analysis are derived. An important feature of the proposed beam element is an advanced modeling capability that originates from individual modeling of each beam layer using cross-sectional elements and layer degrees of freedom, which are embedded in the beam formulation. Complicated layered beam geometries including arbitrary numbers of layers and interlayers, varying and composite cross-sections, and eccentricities can be easily modeled without additional interface elements or constraints. Further, the proposed beam finite element is successfully applicable for predicting geometric and material nonlinear behaviors of the multi-layered beams including nonlinear load-slip relations at interlayers. The superb performance and predictive capability of the proposed beam element are demonstrated through several representative numerical examples.